Key labor law aspects of work - related stress - Molović, Marija (Glasnik Advokatske komore Vojvodine, 2024)
In this paper, the author deals with important labor law aspects of work-related stress, as a type of psychosocial risk, which can be defined as a biopsychological reaction of employees to continuous exposure to pressure, unreasonably demanding or extensive tasks or efforts at work. The main research problem consists in observing the various causes and consequences of stress at work, and the implications that failure to recognize this psychosocial risk has on the health of employees. Although work-related stress is not directly regulated by domestic legal regulations, nor is it treated as an illness, it can damage the employee’s health in multiple ways. The paper analyzes the concept of work-related stress, its causes, consequences and possible legal and other means to prevent it. The paper highlights positive examples from other legal systems regarding prevention and protection from work-related stress. The shortcomings of the domestic system were also pointed out, along with suggestions made de lege ferenda of importance for future changes to existing regulations and practice. The goal of the research is to confirm the initial hypothesis that, due to the lack of appropriate legislation, in practice there is a lack of recognition and prevention of work-related stress, as a risk that threatens the health, safety and overall well-being of employees. Normative, axiological and comparative law methods were applied, a survey and an in-depth interview with employees and employers were conducted.